POLICY IMPLEMENTATION IN IMPROVING TEACHERS’ COMPETENCE AT THE MINISTRY OF RELIGION AFFAIRS OF NORTH SUMATRA PROVINCE - Nurhaizan Nurhaizan (State Islamic University of North Sumatra Indonesia, 2018)
This research aims to determine the extent of efforts to increase the competence of Islamic Religious Education teachers in the Ministry of Religion of North Sumatra Province, especially for Islamic Religious Education teachers who teach in public schools. This is qualitative research, researchers conducted interviews directly with stakeholders involved in efforts to improve teacher competency in the North Sumatra provincial ministry of religion offices, they were Head of Office, Head of the section on Islamic religious education, Head of education and training centers and teachers directly involved in every activity to improve competence. The results of this study have found the following; 1) Increasing teacher competence has become a top priority in the section on Islamic religious education through planning activities such as workshops, training, seminars and direct assistance to teachers. Costs in these activities have been budgeted in the DIPA of the Ministry of Religion of North Sumatra Province each year. 2) The Workshop Implementers and various trainings are the Office of Religious Education and Training of the Province of North Sumatra which specifically has the task of conducting training. 3) Participants involved in the training are all PAI Teachers who teach in public schools. The implementation of these activities is periodically arranged according to needs. Thus, increasing the competence of Islamic Education teachers in the Office of the Ministry of Religion of North Sumatra Province has been programmed and carried out according to the needs